PENANAMAN NILAI MODERASI BERAGAMA DALAM MATA PELAJARAN PAI DI SD NEGERI 215/III DESA KEBUN BARU - Ravico Ravico; Adelia Mela Deza; Anggi Desviana Siregar; Muhammad Alfian; Lia Angela; Tiara Tiara; Pristian Hadi Putra; Fatnan Asbufel (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Religious Moderation Values ​​are values ​​that need to be instilled in a pluralistic environment such as the village of Kebun Baru. As a village that includes various languages, religions and ethnicities, it is important to inculcate the value of moderation. Instilling the value of moderation aims to avoid divisions that may arise due to differences. In this activity of Cultivating the Value of Religious Moderation the author specializes in the 215/III Kebun Baru State Elementary School where students at this school need to know these values ​​from an early age. As for the implementation, the author uses the method of teaching, demonstration, and lecture. The results of this service are instilling the attitude of tawasuth so that students can be honest with themselves and the surrounding environment, the attitude of tasamuh so that students can be respectful of each other, and I'tidal so that students can be consistent and confident in their potential. . With this moderation-based service activity program, it will further strengthen Indonesian unity.